Exact general solutions for the mode shapes of longitudinally vibrating non-uniform rods via Lie symmetries - Nunes, Afonso W. [UNESP]; Silva, Samuel da [UNESP]; Ruiz, Adrian (Elsevier B.V., 2022)
A Lie symmetry method-based approach is proposed for systematically computing general solutions in closed-form for the mode shape equation of non-uniform and unconventional vibrating rods. The mode shape equation is modeled by the elementary rod theory, addressing polynomial, exponential, trigonometric, and hyperbolic cross-section variations. The method provides algorithmic order-reduction steps for solving the investigated mode shape equation, producing a first-order Riccati equation whose integration reveals the aimed solutions for the problem. Illustrative examples are presented, including original solutions in closed-form as well as solutions previously obtained in the literature by other approaches. Mode shapes from general solutions with appropriate rod boundary conditions are also considered for different examples.
Keywords: General solutions; Non-uniform rods; Mode shapes; Elementary rod theory; Lie symmetries